The impact of diet on the inflammatory bowel disease course – a literature review - Agnieszka Nowotarska; Gustaw Błaszczyński; Paweł Nojek; Wiktoria Pawlik; Mariusz Zimonczyk; Monika Zawół; Karolina Jaglarz; Maciej Kuca (Journal of Education, Health and Sport)
Introduction and Objective. Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn’s disease (CD), is a chronic gastrointestinal disorder marked by relapsing symptoms. Current treatments mainly involve immunosuppressive therapies, which are effective but may have significant side effects. Diet as an adjunctive treatment is appealing due to its accessibility, low cost, and minimal adverse effects. This review explores the role of diet in managing IBD, focusing on dietary strategies during both active disease and remission.